PEMBERIAN MELATONIN TERHADAP PASIEN DENGAN GANGGUAN TIDUR - Aisyaa Bintang Shafiera; Inkha Prajadina; Anggraini, Debie (Yayasan Nusantara Hasana Berdikari, 2024)
Sleep is a basic human need and is very important for physical and mental health. The sleep-wake cycle is regulated in a process known as circadian rhythm. Sleep disturbance is an event related to the quality, timing and frequency of sleep. Giving the hormone melatonin in an effort to treat sleep disorders is still under research. This study aims to identify the efficiency of using the hormone melatonin in treating sleep disorders. The method used is a systematic review by collecting existing data. The method used is PRISMA (Preferred Reporting Items For Systematic Reviews and Meta-analysis). The research results come from reviewing data obtained based on research that has been carried out. Providing the hormone melatonin in an effort to overcome sleep disorders has been proven to be effective. However, further research is still needed regarding the use of melatonin in multipathology patients.